KONSEP HUTANG PIUTANG DALAM AL-QURAN (STUDI PERBANDINGAN TAFSIR AL-QURAN AL'AZIM KARYA IBNU KATSIR DAN TAFSIR AL MISBAH KARYA MUHAMMAD QURAISH SHIHAB) - Alfi Amalia (Sekolah Tinggi Ekonomi dan Bisnis Islam (STEBIS) Al-Ulum, 2023)
Debt is a transaction between two parties, one of which gives the money to the other voluntarily to be returned to him by the second party with the same thing. Although we know that debts and debts are permissible, Islam commands its people to avoid debt as much as possible, if they can afford to buy with cash or not in economic hardship. Because debt will always be a heavy burden and endanger morality. Rasulullah saw. Never refused to pray for the corpse of someone who is known to still leave a burden of debt for his family and there is no property to pay these debts. In debt transactions, as described in the Qur'an, first it must be recorded or written. In relation to the parties who did the writing, Quraish Shihab and Ibn Kathir in their Tafsir, both of them have the view of writing or recording accounts payable that it is the debtor who dictates to the scribe regarding the debt he admits, this is feared by the occurrence of fraud against the debtor. Second, there must be a fair witness. In terms of this testimony, Quraish and Ibn Kathir agree. If the transaction is in the form of buying and selling, then it is permissible without recording or writing. According to Ibn Kathir, that in the matter of testimony, the law of being a witness is fardlu kifayah or it is not mandatory for the person concerned, except if there is no other person who can replace his position. Meanwhile, according to M. Quraish Shihab, this order (to be a witness) is a recommendation, especially if someone else gives information, and it is only obligatory if the testimony is absolutely necessary to uphold justice